Fibra de vidrio y sus diferentes aplicaciones en el sector constructivo de la ingeniería civil (2021)
This article is carried out in order to collect information about the application of glass fibers in civil engineering works and the manner in which the mechanical properties of the different construction materials behave by including this composite material as a reinforcement, in addition to being relatively less expensive than other types of fiber and some conventional materials. This has allowed more and more to include this material in the world of construction with various applications such as: masonry, concrete, pipes, bridges among others. In the same way we analyze each of the characteristics specifically the durability and types of fiberglass existing, because it is to know that to obtain a better use of this materialmade with Silica-based (SiO2). It is important to make a good choice of the type of the same, depending on the structure or material to be carried out.